Magnetorheological Elastomer Stiffness Control for Tunable Vibration Isolator - Gigih Priyandoko; Tedi Kurniawan; Efistein Naga (IAES Indonesia Section, 2018)
Most of the vibration isolator has fixed stiffness such as passive vehicle mounting system. Objective of this research is to develop a Magneto-rheological Elastomer (MRE) as a vibration isolator when different currents are applied to get different stiffness of the MRE. A MRE was fabricated by mixing silicon rubber, silicon oil and carbonyl iron particles together and then cured for 24 hours in a circular mold. Experimental result shows that that there were decreases in amplitude of the vibration in time and frequency domains when the current applied to the coil is increased.